(untitled) (Research, Society and Development, 2023)
Mastitis is one of the main diseases that affect goats, especially when it comes to dairy animals. The main objective of this review is to provide information on goat mastitis, taking into account epidemiological, microbiological aspects, clinical signs and forms of treatment, based on data found in the described literature, with works being selected according to the subject covered. Mastitis can be caused by several etiological agents, among which Staphylococcus spp stands out as the most important. Several factors can trigger mastitis, including lack of milking management and poor hygiene measures, which generate clinical or subclinical mastitis. As a form of diagnosis, somatic cell quantification and the California Mastitis Test are used. Treatment is mainly based on clinical aspects, however there are new effective alternatives that can facilitate the control of these microorganisms, as well as the use of essential oils. At the end of this review, it was possible to conclude that breast changes caused by mastitis in goats can generate problems that include the health of the animal and consequently the economic profitability of the producer, however, despite the increase in research on mastitis in goats, there is still a shortage of information focused on this species.